Correlation analysis between semen routine parameters and sperm DNA fragmentation index in patients with semen non-liquefaction: A retrospective study - Ji Fengqing; Chen Junying; Lin Liyun (Open Life Sciences)
This research investigated the correlation between routine semen parameters and the sperm DNA fragmentation index (DFI) in infertile males with non-liquefying semen, aiming to provide insights for infertility management. We conducted a retrospective analysis of 152 infertile males at our Andrology Department from March 2023 to March 2024, assessing differences in semen parameters and DFI based on liquefaction times and identifying influential factors on DFI. Participants were divided into two groups based on their semen liquefaction times: less than 60 min (111 patients) and 60 min or more (41 patients). The group with normal liquefaction times demonstrated significantly better forward and total sperm motility, and lower sperm morphology indices and DFI values. A positive correlation was found between DFI and liquefaction time, while a negative correlation was observed with motility and normal sperm ratio. Specifically, each additional minute of liquefaction time increased DFI by 0.13, and a 1% decrease in normal sperm ratio increased DFI by 0.73. The findings indicate that delayed semen liquefaction correlates with poorer sperm motility and morphology and higher DFI, underscoring the importance of comprehensive semen assessment in evaluating male fertility.